PELAKSANAAN PROGRAM KEGIATAN BKL MELATI DI KELURAHAN SEKAR MAWAR KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Rafianti, Wetri; Jas, Jaspar; widiastuti, widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the implementation of BKL Melati program activities in Sekar Mawar Village Pasir Penyu Sub-district Indragiri Hulu Regency. This research uses qualitative research method and uses descriptive approach that aims to provide a systematic description of the ongoing situation on the object of research that is the implementation of the program of elderly family development activities in the village sekar rose district turtle sand district indragiri upstream. As a reference to conduct research in the field, researchers prepare a grid in the form of questions to be presented interview materials to respondents. The results of this study on the implementation of the program of elderly family development activities in the village sekar roses turtle sand districts of indragiri upstream has been implemented well enough but still there are shortcomings, starting from: a) The meeting to-1 physical coaching elderly in BKL Melati has been implemented which began from the gymnastics activity is the first process of praying, singing mars BKL, humming elderly and after that the cadres provide counseling or direction to the elderly then continued with gymnastics, and in this activity the elderly are very participate, also found the constraints of the fund and the elderly itself. b) The second meeting of elderly reproductive health counseling in BKL Melati is by giving counseling of cervical kankaer and menapause by cadres and from puskesmas so that elderly understand cadre explain by using media of poster and picture. c) The 3rd meeting of psychological counseling of elderly in BKL Melti is very important for elderly because of elderly age which is very susceptible to sensitive and easily offended by this counseling elderly can control their own emotions also this coaching to mempesrsiapkan elderly in his old age and build elderly to stay harmonious with his family, this coaching is implemented diposyandu or BKL Melati.Keywords: Program Implementation, BKL